Problems and solutions in stochastic calculus with applications - Albin, Patrik; Hamza, Kais; Klebaner, Fima C. (New Jersey : World Scientific, 2025)
"Problems and Solution in Stochastic Calculus exposes readers to distinct simple ideas and proofs in stochastic calculus and its applications. It is intended as a companion to the successful original title Introduction to Stochastic Calculus with Applications (3rd Edition) by Fima Klebaner. The current book is authored by three active researchers in the fields of probability, stochastic processes, and their applications in financial mathematics, mathematical biology, and more. The book features problems rooted in their ongoing research. Mathematical finance and biology feature pre-eminently, but the ideas and techniques can equally apply to fields such as engineering and economics. The problems set forth are accessible to students new to the subject, with most of the problems and their solutions centring on a single idea or technique at a time to enhance the ease of learning. While the majority of problems are relatively straightforward, more complex questions are also set in order to challenge the reader as their understanding grows. The book is suitable for either self-study or for instructors, and there are numerous opportunities to generate fresh problems by modifying the ones presented, facilitating a deeper grasp of the material"--
Includes index.
Keywords: Stochastic analysis; Stochastic processes; Calculus